Experimental Centrifuge Study of the Effects of Valley Topography on the Behavior of a Concrete Face Rockfill Dam - Chao Tian; Xuedong Zhang; Lifeng Wen (Advances in Civil Engineering)
The recent focus on water conservancy projects globally has resulted in the construction of increased numbers of concrete face rockfill dams in narrow valleys. However, valley topography impacts the deformation of a dam and further influences the distribution of stress and position of cracks on the face slab. This study conducted two centrifuge experiments to study the influence of the valley topography on the behavior of a concrete face rockfill dam from construction to impoundment. Experimental models of concrete face slab sand-gravel dams with “U”-type and “V”-type valley topographies were established. The settlement of the dam crest, the displacement of the upstream slope of the dam, and the stress on both sides of the face slab were observed. The experiment also represented the cracking of the face slab during impoundment. The results showed that the “V”-type valley topography effectively reduced the progression of dam crest settlement and influenced stress on the slab resulting from impounded water pressure. Furthermore, the flexural form of the face slab in the “U”-type valley topography took on a “D” shape and cracks progressively developed on the face slab with increased water load. The flexural form of the face slab in the “V”-type valley topography showed a “B” shape, and cracks occurred under a particular water impoundment pressure.